National Social Science Documentation Centre: Reflections and Suggestions - Ranganathan, S. R. (Journal of Information and Knowledge, 1972)
The attempts made since 1959, to establish a National Documentation Centre for Social Sciences are described. The difficulties due to the absence of stabilised Standard Terminology in the Social Sciences and the unfamiliarity of the documentalists in Social Sciences with the Standard Terminology in Documentation are mentioned. The right functions of a National Documentation Centre are described. The primary function of a National Documentation Centre is emphasised to be the publication of an advance national documentation periodical. The procedure for the preparation and publication of a Union Catalogue of Learned Periodicals and Serials is described in detail. A National Documentation Centre should not by itself maintain the national library in its subject field. Delegation of national documentation work to regional centres is unhelpful. Right delegation should be to national documentation centres in charge of the different subject fields in Social Sciences, when the time is ripe for it.